Validation Instruments for the Development of Cooperative Module Based On Student Facilitator and Explaining Type in Courses Powertrain System - Rahma Doni; Wagino Wagino; M Nasir; Wakhinuddin S; Suhendar Suhendar (Universitas Sultan Ageng Tirtayasa, 2022)
The lack of maximum understanding of students, especially on powertrain system subjects marked by low student learning outcomes, allegedly occurs because the available teaching materials have not been able to facilitate students to be able to learn independently and thoroughly and learning is still focused on educators as the main source of teaching materials. The main reason the researcher conducted this development research. This study aims to determine and test whether the module developed is valid or not to be used as teaching material in the powertrain system course. This development research uses a 4D model (Define, Design, Develop and Disseminate). The subjects of this study were students of Heavy Equipment Engineering at the Sawahlunto State Community Academy. The type of data is primary data where the data is provided by expert lecturers and students. The data collection instrument is in the form of a questionnaire. The data analysis technique used is descriptive data analysis technique, namely by describing the validity of the module based on this type of Student Facilitator and Explaining Cooperative. After doing the research, it was found that the cooperative module of the Student Facilitator and Explaining type was declared valid in the material aspect with a validity value of 85% and was declared valid in the format aspect with a validity value of 83%. Based on the findings of this study, it was concluded that the Student Facilitator And Explaining Cooperative-Based module was valid to be used as a learning medium in the Powertrain System course.